Unlocking sustainable competitive advantage in healthcare: How workplace values, service culture, and capabilities drive excellence in hospitals - Susilowati, Kristiana; Suharti, Lieli; Sugiarto, Agus (Edelweiss Applied Science and Technology, 2025)
The study investigates the way in which Christian hospitals integrate faith-based values into their management structures in order to develop distinctive service competencies and gain long-term competitive advantage in increasingly competitive healthcare markets. Phenomenological qualitative inquiry entailed conducting in-depth interviews with ten Indonesian Christian hospital senior leaders. Thematic analysis was employed to analyze recurring patterns and relationships between spiritual bases, integration processes, and competitive outcomes. Four integration mechanisms are identified by the study: mission-based leadership, spiritual community building, values-based care provision, and open-ended stakeholder dialogue. These mechanisms build distinctive service capabilities that bridge spiritual foundations and competitive success. Christian values, when incorporated into organizational practices through a structured approach, create one-of-a-kind competitive strengths with the hospital retaining its spiritual mission orientation and nature. Hospital administrators must effectively balance mission accomplishment with economic sustainability. The conceptual framework presents prescriptive recommendations for faith-based healthcare organizations to leverage their religious identity as an asset in challenging healthcare settings.